Water impact on the auto-ignition of kerosene/air mixtures under combustor relevant conditions. (1st May 2020) - Sun, Wuchuan; Huang, Wenlin; Qin, Xiaokang; Deng, Yuanhao; Kang, Yudong; Peng, Weikang; Zhang, Yingjia; Huang, Zuohua
Highlights: New ignition data of RP-3/air mixtures with various H2 O concentrations were provided. A four-component surrogate of RP-3 and corresponding kinetic model were proposed. H2 O concentration-dependence of RP-3 reactivity was explored. The effects of thermodynamics and kinetics of H2 O were well distinguished. Abstract: Impact of water (H2 O) vitiation on auto-ignition characteristics of kerosene/air mixtures was investigated behind the reflected shock waves covering pressures of 0.45–7.5 atm and temperatures of 900–1450 K. Arrhenius-type expressions were fitted for both mixtures with and without H2 O using multiple linear regression method. Temperature- and pressure-dependences of ignition delay times were experimentally observed to be in-line with conventional hydrocarbons for all the test mixtures, but stronger pressure-dependence exhibited when presence of H2 O. A four-component surrogate model fuel (25.7% n -tetradecane/23.0% 2-methylundecane/42.1% n -butylcyclohexane/9.2% n -butylbenzene) was proposed based on similarity criterion of function group. A surrogate mechanism was subsequently assembled by incorporating the modified rate rule of certain reaction class. The proposed kinetic model reproduces well the experimental observations at the entire conditions. Thermal and kinetic effects of H2 O on the RP-3 reactivity were distinguished by factitiously inducing a weak collision H2 O* and an inert H2 O**. Results reveal that the kinetic-based promotion of H2 O outweighs the thermal-based inhibition on the RP-3 reactivity at high pressures due to higher collision efficiency, which facilitates the reaction H2 O2 (+M) ⟺ OH + OH (+M). However, the RP-3 reactivity is inhibited only by thermodynamics without kinetics at low pressures.